Analisis Strategi Pertumbuhan dan Penetrasi Pasar pada Usaha Bakso Bakar UMKM - Mhd. Hanif Rhizwan; Fadli Agus Triansyah; Khafi Puddin (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the growth strategy and market penetration implemented in a micro, small, and medium enterprise (UMKM) engaged in the culinary sector, specifically a grilled meatball (bakso bakar) business. The background of this research is based on the increasing competition among street food businesses, which requires business actors to adopt appropriate strategies to maintain and improve their market position. This research uses a qualitative descriptive method by collecting data through observation and documentation of business activities, including pricing strategies, service quality, product value proposition, and marketing practices. The results show that the business applies a market penetration strategy by focusing on increasing sales of existing products in the same market segment without significant product innovation. Key efforts include selecting strategic selling locations, offering competitive prices, maintaining consistent taste quality, improving service speed, and providing promotional incentives such as discounts and bonuses. In addition, strengthening the value proposition through unique flavors, affordable pricing, and customer-oriented service contributes to customer satisfaction and repeat purchases. The findings indicate that market penetration is an effective and low-risk strategy for small-scale culinary businesses with limited resources. The implication of this study suggests that UMKM actors can optimize their business performance by focusing on simple yet consistent marketing strategies and enhancing customer experience to build long-term loyalty.